Corporate contribution in the health sector: the case of Bangladeshi banking companies - Hossain, Dewan Mahboob; Mohamad Diah, Nurazzura (medi+WORLD Internationa, 2014)
This study examines the contribution of the corporate sector in the healthcare sector of a developing economy - Bangladesh. In order to fulfil this objective, the researchers focused on the contribution of the banking sector through six case studies. The annual reports of the banks were taken as the sources of data. Content analysis of these annual reports was conducted. It was seen that in many ways, the companies in the banking sector of Bangladesh are trying to contribute to the healthcare sector of Bangladesh. From the context of a poor country, these attempts can be considered as praiseworthy.